The Impact of Remittances on Food Inflation in Bangladesh: An ARDL Approach - Rahman, Ashiqur; Afroza Akter Sumi; Sadekin, Md Nazmus (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose of the study: This study aims to investigate how Bangladesh’s food inflation is affected by remittance influx. Methodology: The analysis utilizes secondary data collected from 2005 to 2022. In order to accomplish the goals, this study employs the food inflation rate as an endogenous variable, while workers’ remittance, official exchange rate, and broad money supply are used as exogenous factors. The data is sourced from the World Development Index (WDI). In this investigation, co-integration is assessed using the Autoregressive Distributed Lag (ARDL) model to provide an accurate outcome. Findings: The study’s findings show that, both in the short and long term, the influx of remittances from migrants has a positive and considerable impact on driving up food inflation. This analysis shows that while having a negative short-term impact, the money supply and exchange rate have a long-term, positive, and considerable influence on food inflation. Application of the Study: This research proposes that promoting agricultural output and motivating recipients of remittances to invest in income-generating activities can effectively reduce their reliance on food consumption. If these recommendations are effectively followed, the inflow of workers’ remittances will have a positive impact on the economy and contribute to reducing inflationary challenges. Originality of the study: By employing the most recent data set and cutting-edge methodology, the present research adds to the body of available research by demonstrating a link between food inflation and remittances.